Study on Hydrological Drought Forecasting Based on SWAT Model and ESP Thought - SUN Long; LI Meng (Renmin Zhujiang)
Based on measured data such as 40-year long series of hydrological and meteorological data from 1970 to 2009,and the distributed hydrological model SWAT with strong mechanism and integrated forecasting ESP thought,this paper builds a set of drought forecasting system,optimizes the parameters of SWAT model by data from 1970 to 2009,predicts the future long-term (April to October,2010) hydrological drought in the middle and lower reaches of Ganjiang,and calculates and predicts the probability of occurrence of hydrological drought from early April 2010 to late October 2010 in a ten-day basis with ten-day runoff depth anomaly percentage as the early warning indicator for judging the hydrological drought in various districts and counties.The results show that,hydrologic drought is more likely in the middle of May,middle of June to late July,middle of August,early September and middle of October to late October, among which a wide range of hydrological drought is likely to happen in early to middle of July and middle to late October.The predicting results can provide scientific guidance for drought resistance and disaster reduction.